An Analysis of the Communication of Provincial Identities in Mascots to Promote Tourism in Thailand - Suchada Wattanarak (Institut Pertanian Bogor, 2021)
This research analyzed the communication of provincial identities in mascots to promote tourism in Thailand through the conceptual frameworks of semiotic theory and identity concept. It is a qualitative research using an analysis of mascot components, an analysis of provincial identities that appear in the mascots, and in-depth interviews. The tools used consisted of a symbolic component analysis table with provincial identities and in-depth interviews.The sample group consisted of 23 mascots and 5 policymakers and mascot designers.Results of the study revealed that senders use mascots that are cute, friendly, and straightforward. Most of the senders use the encoding of sign in the icon level that looks like or resembles real objects to make them interesting and easy to understand. In addition, there is the encoding of sign in the index level that is reduced from real objects into patterns of costumes and accessories that make the mascots stand out. In terms of provincial identities, it was found that the meanings of the various symbols are transmitted in the dimensions of bringing up the distinctive identities of the province in seven aspects: 1) traditions and beliefs, 2) archaeological sites and antiques, 3) food and products, 4) famous tourist attractions, 5) costumes, 6) art and culture, and 7) other identities.